Designing Tangible 3D Printed Cathode Ray Oscilloscope in Learning Electronic for Physics in Secondary School - Muhammad Fadhly Ahlamie Md Nor 'Azam; Wafry Khairul Ziad; Harika Kaco; Mohd Shaiful Sajab; Fadzidah Mohd Idris; Nurhidaya Mohamad Jan; Nor Raihan Zulkefly; Siti Munirah Mohd (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 93-96